The complete mitochondrial genome of the springtail Allacma fusca, the internal phylogenetic relationships and gene order of Symphypleona. Issue 3 (2nd July 2020) - Nardi, Francesco; Cucini, Claudio; Leo, Chiara; Frati, Francesco; Fanciulli, Pietro Paolo; Carapelli, Antonio
Abstract: Symphypleona ( sensu stricto ) are a group of Collembola (=springtails) that, despite displaying some variation in gene order, have been poorly investigated under the phylomitogenomic perspective. How families and subfamilies of this taxon are evolutionary related is still partially unknown. For this reason we sequenced, and herein described, the complete mitochondrial genome sequence of Allacma fusca (Sminthuridae). This sequence, alongside others from the literature, is here used to study the phylogenetic relationships among Symphypleona.